How Attribution of COVID-19 Crisis Responsibility Predicts Hong Kong Citizens’ Intention to Accept Vaccination - Ji Won Kim; Qinxian Cai; Lang Kao; Yi-Hui Christine Huang (Vaccines)
Background: This study aims to illuminate the role of perceived crisis responsibility in shaping vaccination intention. By using the case of Hong Kong during the COVID-19 pandemic, we examined whether and how the allocation of crisis responsibility to the government predicts the public’s intention to take vaccines, particularly by investigating its underlying mechanism. Method and Results: Based on a population-representative sample of Hong Kong adults (N = 3188), our results indicated that (1) the attribution of crisis responsibility directly led to lower vaccination intention, and (2) it also had indirect influences on vaccination intention through trust and anger; specifically, the crisis attribution resulted in less willingness to take vaccines via a decreased trust in government health agencies. We also found a serial mediation pathway in which anger aroused by the crisis attribution could decrease trust, which, in turn, yielded lower vaccination intentions. Conclusion: The findings of this study offer theoretical insights into the role of attribution of crisis responsibility in affecting vaccination decisions during a public health emergency. Further, these findings provide directions for crisis managers and public health authorities to develop communication strategies to motivate vaccine uptake and formulate an approach to tackle the pandemic crisis.